Design and Fabrication of Portable Bladeless Fan - Manavalan, S.; Ranjan, Kumud; Kumar, Lalan; Kumar, Manish; Kumar Rai, Manish (International Journal of Psychosocial Rehabilitation, 2019)
The aim is to provide cool breeze-type air without having blades. According to the current situation, fans play an important role in our day-to-day lives. It is the most important thing for releasing stress. Due to this equipment, human beings can continuously work without any stress for a longer period. The project deals with a portable bladeless fan with improved cooling. The cooling is done without rotating the blades. No blades are present in the fan. Only a round hollow spherical curve is present. A bladeless fan is a high-technology invention with unusually innovative characteristics. It doesn't have any visible blades, thus completely safe. The bladeless fan is fully variable. Air Multiplier Technology draws air at very high speed and compresses it. Due to this equipment, human beings can continuously work without any stress for a longer period. The project deals with a portable bladeless fan with improved cooling.